Micromechanical Model of Dry Friction Hybrid Polymer Composite Clutch Facings - Biczó, Roland; Kalácska, Gábor (International Journal of Engineering and Management Sciences, 2019)
Modelling the complex coupled thermomechanical and tribological contact of a dry friction clutch system between cast iron flywheel and scatter-wound hybrid composite clutch facing requires a thought through investigation of the friction material properties and behaviour. Challenges of the creation of a mechanical stiffness matrix for such a complex material are described in this paper along with simplification ideas and solutions.